2022
DOI: 10.3390/agriculture12020289
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Use and Resistance in Plant Agriculture: A One Health Perspective

Abstract: Bactericides, fungicides, and other pesticides play an important role in the management of plant diseases. However, their use can result in residues on plants and in the environment, with potentially detrimental consequences. The use of streptomycin, oxytetracycline, copper-based products, and some fungicides is correlated with increased resistance among plant pathogens to these agents. Likewise, the recent rise in the incidence of environmental triazole fungicide-resistant Aspergillus fumigatus, the cause of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(64 citation statements)
references
References 134 publications
1
63
0
Order By: Relevance
“…Antibiotic and AMR spread through the food chain, into the environment, to wildlife and humans were also identified as driving AMR as others have found ( Bondad-Reantaso et al, 2012 ; Holmes et al, 2016 ; Stålsby Lundborg and Tamhankar, 2017 ; Zellweger et al, 2017 ; Ng et al, 2018 ). Consistent with others ( Gupta, 2012 ; Laohaudomchok et al, 2021 ), our study found pesticide use in food production in SEA, which can contribute to AMR via the natural environment (e.g., soil; Malagón-Rojas et al, 2020 ; Miller et al, 2022 ), reinforcing calls to better understand how soil, water, and pesticides interrelate to generate and spread AMR ( Miller et al, 2022 ). Other participants identified social factors influencing AMR in SEA which are also found in the literature, and included: lack of awareness about AMR, antimicrobials and their proper use among the public, food service industry, prescribers, drug sellers, farmers, and knowledge brokers, such as government officers; inappropriate prescribing practices; and access to antibiotics or antimicrobials through public, private, and unregulated supply chains ( Puspitasari et al, 2011 ; Islahudin et al, 2014 ; Nga et al, 2014 ; Om et al, 2017 ; Zellweger et al, 2017 ).…”
Section: Discussionsupporting
confidence: 89%
“…Antibiotic and AMR spread through the food chain, into the environment, to wildlife and humans were also identified as driving AMR as others have found ( Bondad-Reantaso et al, 2012 ; Holmes et al, 2016 ; Stålsby Lundborg and Tamhankar, 2017 ; Zellweger et al, 2017 ; Ng et al, 2018 ). Consistent with others ( Gupta, 2012 ; Laohaudomchok et al, 2021 ), our study found pesticide use in food production in SEA, which can contribute to AMR via the natural environment (e.g., soil; Malagón-Rojas et al, 2020 ; Miller et al, 2022 ), reinforcing calls to better understand how soil, water, and pesticides interrelate to generate and spread AMR ( Miller et al, 2022 ). Other participants identified social factors influencing AMR in SEA which are also found in the literature, and included: lack of awareness about AMR, antimicrobials and their proper use among the public, food service industry, prescribers, drug sellers, farmers, and knowledge brokers, such as government officers; inappropriate prescribing practices; and access to antibiotics or antimicrobials through public, private, and unregulated supply chains ( Puspitasari et al, 2011 ; Islahudin et al, 2014 ; Nga et al, 2014 ; Om et al, 2017 ; Zellweger et al, 2017 ).…”
Section: Discussionsupporting
confidence: 89%
“…However, it should be considered that in nature strains tagged with antibiotic resistance can pose serious concerns regarding the possible spread of antibiotic resistance genes in the environment due to horizontal gene transfer. Consequently, the deliberate release of PGPB tagged with antibiotic resistance genes is not recommended [ 93 , 94 ].…”
Section: Techniques To Study Plant-pgpb Interactionsmentioning
confidence: 99%
“…Pesticides such as bactericides and fungicides that are commonly used in agriculture could persists in soil and became a potential AMR reservoir. Aspergillus fumigatus is one of the fungi that caused aspergillosis in human that showed resistant to the triazole medication ( Miller et al, 2022 ). According to Rybak et al (2019) , gene mutation cyp51A is the potential cause that contributes to the fungus resistance to the drug.…”
Section: Effect Of Antimicrobial Resistance To the Environmentmentioning
confidence: 99%